ASTP: MODEL PEMBELAJARAN BAHASA ASING BAGI MILITER - Nasution, A. Sayuti Anshari (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
The United States Army during the Second World War stunned the education world with their foreign language teaching experience. Their program that is called â€œThe Army Specialized Training Programâ€ (ASTP) was able to successfully train many participants with a very high success rate. Dr. Hamada Ibrahim, a professor in foreign languages at Cairo University, Egypt, described the â€œASTPâ€ as the most immense and successful program of learning foreign language in the history. The US Army foreign language program encompasses the background for the emergence of this program, a general picture of the program, the teaching subjects as well as the teaching techniques.